Essential role of Msx1 in regulating anterior-posterior patterning of the secondary palate in mice. (January 2022) - Zhu, Shicheng; Song, Hanjing; Zhong, Liangjun; Huo, Suman; Fang, Yukun; Zhao, Wanxin; Yang, Xueqin; Dai, Zhong-Min; He, Rui; Qiu, Mengsheng; Zhang, Zunyi; Zhu, Xiao-Jing
Abstract: Development of the secondary palate displays molecular heterogeneity along the anterior-posterior axis; however, the underlying molecular mechanism remains largely unknown. MSX1 is an anteriorly expressed transcription repressor required for palate development. Here, we investigate the role of Msx1 in regional patterning of the secondary palate. The Wnt1-Cre- mediated expression of Msx1 ( RosaMsx1 Wnt1-Cre ) throughout the palatal mesenchyme leads to cleft palate in mice, associated with aberrant cell proliferation and cell death. Osteogenic patterning of the hard palate in RosaMsx1 Wnt1-Cre mice is severely impaired, as revealed by a marked reduction in palatine bone formation and decreased expression of the osteogenic regulator Sp7 . Overexpression and knockout of Msx1 in mice show that the transcription repressor promotes the expression of the anterior palate-specific Alx1  but represses the expression of the medial-posterior palate genes Barx1, Meox2, and Tbx22 . Furthermore, Tbx22 constitutes a direct Msx1 target gene in the secondary palate, suggesting that Msx1 can directly repress the expression of medial-posterior specific genes. Finally, we determine that Sp7 is downstream of Tbx22 in palatal mesenchymal cells, suggesting that a Msx1/Tbx22/Sp7 axis participates in the regulation of palate development. Our findings unveil a novel role for Msx1 in regulating the anterior-posterior growth and patterning of the secondary palate.